Structure and properties of nanocrystalline iron oxide powder prepared by the method of pulsed laser ablation - Svetlichnyi, Valerii A. (Russian physics journal)
Colloidal solution of iron oxide nanoparticles is synthesized by nanosecond pulsed laser ablation (Nd:YAG laser, 1064 nm, 7 ns, and 180 mJ) of a metallic iron target in water, and nanocrystalline powder is prepared from this solution by vacuum drying. A composition and structure of the material obtained are investigated by methods of electron microscopy, x-ray diffraction, and optical spectroscopy. It is established that oxide particles with average size of about 5 nm and Fe3O4 magnetite structure are mainly formed during ablation. Preliminary investigation of magnetic properties of the prepared nanoparticle powders shows that they can be in ferromagnetic and/or superparamagnetic states. @ 2017 Springer Science+Business Media New York.